2017
DOI: 10.1590/1807-1929/agriambi.v21n2p106-110
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic efficiency, gas exchange and yield of castor bean intercropped with peanut in semiarid Brazil

Abstract: A B S T R A C TTo evaluate the photosynthetic efficiency, gas exchange and yield of castor bean intercropped with peanut under Brazilian semiarid conditions, a field experiment was set up with six treatments and four replicates arranged in a randomized block design. The experiment consisted of the cultivation of castor bean 'BRS Energia' in a monocrop system and intercropped with peanut 'BR 1' . One treatment was formed by monocropped castor bean and the others by the castor bean intercropped with peanut with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…LAI has been shown to be an effective method by which to evaluate light absorption, and the photosynthetic rate of a crop is directly affected by the LAI 29 , 32 . We found that the LAI of intercropped soybean and maize are lower than that of the corresponding sole crop, indicating that the two species restrained each other in LAI of the competing crop when intercropped 33 . The DIFN was significantly improved under intercrops, showing that intercrop increased light transmission of the canopy and decreased the waste of light energy 34 .…”
Section: Discussionmentioning
confidence: 77%
“…LAI has been shown to be an effective method by which to evaluate light absorption, and the photosynthetic rate of a crop is directly affected by the LAI 29 , 32 . We found that the LAI of intercropped soybean and maize are lower than that of the corresponding sole crop, indicating that the two species restrained each other in LAI of the competing crop when intercropped 33 . The DIFN was significantly improved under intercrops, showing that intercrop increased light transmission of the canopy and decreased the waste of light energy 34 .…”
Section: Discussionmentioning
confidence: 77%
“…In addition, the correlation of yield with g s and photosynthesis when these values were averaged through the drought period was higher than the correlation between yield and seed Δ 13 C (Figures 2–5). This was surprising because in previous research, the correlation between yield and gas exchange measurements has been reported as weak (Dutra et al., 2017; Zheng et al., 2011). The high correlation observed in our study is likely the result of averaging the abundant and repeated measurements during the drought period.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, seed Δ 13 C showed a stronger positive relationship with yield than shoot biomass (Figures 2 and 3), similar to what has been found in common bean (Polania et al., 2016; Sanz‐Saez et al., 2019). This would indicate that seed Δ 13 C is a better parameter than shoot Δ 13 C to predict yield; however, studies in soybean have demonstrated that shoot and seed Δ 13 C can both be used to predict yield (Dutra et al., 2017; Kaler et al., 2018). The low correlation between shoot Δ 13 C and yield observed in our study (Figures 2 and 3) was likely due to the fact that the samples were taken at harvest and at that point some of the 13 C fixed in the shoot may have already been transported to the reproductive organs (Kvien et al., 1986; Zhou et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is important emphasize that K is a primary element to several plants' physiological actions, such as cellular turgor control, activation of enzymes involved in respiration, water relations, photosynthesis and adjustment of stomatal opening and closuring [24]. This nutrient also acts on the regulation of stomatal conductance mechanism, which controls the water use efficiency (increasing its efficacy), considering that the use of water molecules becomes more efficient [25]. This is why plants usually use mechanisms of adaptation in order to reduce transpiration, increase carboxylation efficiency and improve its water use [26].…”
Section: Biofertilizermentioning
confidence: 99%